The influence of boundary layer on the growth kinetics of carbon nanotube forests. (November 2015) - Lee, Jaegeun; Oh, Eugene; Kim, Teawon; Sa, Jeong-Hoon; Lee, Sung-Hyun; Park, Junbeom; Moon, Dustin; Kang, In Seok; Kim, Myung Jong; Kim, Seung Min; Lee, Kun-Hong
Abstract: The growth of carbon nanotube (CNT) forests has been limited to the centimeter scale due to insufficient understanding of their growth kinetics. To investigate the growth kinetics of CNT forests, we characterized the mass transport phenomena arising during CNT forest. We formulated the hypothesis that such growth is mass transport limited and proposed a model describing this mass transport. According to our model, the effects of diffusion boundary layers on the growth rate are significant. The initial growth rate is expected to increase with the velocity of the bulk gas flow as the boundary layer thickness decreases. To test this prediction, CNT forests were grown at various total gas flow rates in the range 170–1700 sccm, which correspond to flow velocities in the range 0.79–to 7.9 cm/s. The initial growth rate was found to increase from 1.4 mm/h to 3.5 mm/h as the total flow rate increases from 170 sccm to 1700 sccm. Thus there is a clear inverse proportionality between the initial growth rate and the thickness of the diffusion boundary layer, which confirms that the growth of CNT forests is mass transport limited. These results provide new insight into the growth kinetics of CNT forests.